The Efficacy and Safety of Multiple Dose Regimens of Kudzu (Pueraria lobata) Root Extract on Bone and Cartilage Turnover and Menopausal Symptoms - Bihlet, Asger Reinstrup; Byrjalsen, Inger; Andersen, Jeppe Ragnar; Simonsen, Simone Faurholt; Mundbjerg, Kamilla; Helmer, Betina; Riis, Bente Juel; Karsdal, Morten Asser; Christiansen, Claus (Frontiers in Pharmacology, 2021)
Background: Menopause is associated with detrimental changes in turnover of bone and cartilage and a variety of symptoms with negative impact on the quality of life. Naturally occurring isoflavones from Radix Pueraria lobata, Kudzu root, may possess chondroprotective and symptom-relieving properties, but efficacy and safety of dosing and dose frequencies required for pharmacological action is unclear. Purpose: This clinical trial evaluates the efficacy on bone and cartilage turnover, menopausal symptoms, and safety of five dose regimens of Kudzu root extract administered either once, twice or three times daily in women with at least mild menopausal symptoms. Materials and Methods: Fifty postmenopausal women were randomized equally into five different dose regimen groups of Kudzu root extract in a four-week, parallel group, open-label, single-center, exploratory study design. Biomarkers CTX-I and CTX-II reflecting bone and cartilage degradation, respectively, were assessed in blood samples and 24-hour urine samples. Change from baseline in the Menopause Rating Scale (MRS) and subscales was evaluated. Safety endpoints were frequency of adverse events, changes in hematology and safety chemistry data, vital signs and electrocardiogram. Results: Fifty women (Age 54.2 years, SD: 2.9) were randomized. After four weeks of treatment, biomarkers of bone resorption and cartilage degradation were statistically significantly reduced from baseline levels in the group receiving two capsules three times a day, serum/urine CTX-I (-18.4%, 95 % CI: -8.1 to -27.5, p=0.001/-34.2%, 95 % CI: -21.6 to -44.7, p<0.0001), urine CTX-II (-17.4% 95% CI: -2.5 to -30.0, p=0.02). The observed effects were consistent across study groups but appeared to favour three times daily dosing. Four weeks of treatment led to statistically significant reductions in the MRS Total Score (p<0.0001-0.03) in four out of five treatment groups. Kudzu root extract was well tolerated in all dose regimens, and no serious adverse events were reported. Conclusion: The results indicate that Kudzu extract may possess beneficial effects on bone and cartilage health and may be a promising natural alternative to existing treatments for menopausal symptoms. Kudzu root extract was well tolerated for short-term treatment of mild to severe menopausal symptoms in women in all tested doses and dose frequencies